1993
DOI: 10.2307/2152936
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Evidence for Small Generating Sets

Abstract: Abstract.For an integer n , let G(n) denote the smallest x such that the primes < x generate the multiplicative group modulo n . We offer heuristic arguments and numerical data supporting the idea that G(n) < (log2)_1 lognloglog« asymptotically. We believe that the coefficient 1 / log 2 is optimal. Finally, we show the average value of G(n) for n < N is at least(1 + o( 1 )) log log N log log log N, and give a heuristic argument that this is also an upper bound. This work gives additional evidence, independent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 15 publications
(20 reference statements)
0
12
0
Order By: Relevance
“…Let G(n) be the smallest integer k such that the primes p ≤ k generate the multiplicative group modulo n. Prove or disprove the conjectures formulated by Bach and Huelsbergen [24], see §9.7.55.…”
Section: )mentioning
confidence: 93%
See 3 more Smart Citations
“…Let G(n) be the smallest integer k such that the primes p ≤ k generate the multiplicative group modulo n. Prove or disprove the conjectures formulated by Bach and Huelsbergen [24], see §9.7.55.…”
Section: )mentioning
confidence: 93%
“…Narkiewicz [384] sharpened this estimate to O(x 1−A/(log 2)+ǫ ). Ram Murty and Srinivasan [379] considered a sum akin to (24). They showed that if…”
Section: )mentioning
confidence: 99%
See 2 more Smart Citations
“…A proof of an explicit bound such as r/log r ≤ 2 lg x would imply, among other things, that there is a deterministic primality-proving algorithm taking essentially cubic time. See [8], [2], [14, Another way to phrase the same result: Every non-square positive integer below 24 · 2 64 is locally non-square at some prime in {2, 3, . .…”
Section: Doubly Focused Enumerationmentioning
confidence: 99%